Recruiting, interviewing, selecting & orienting new employees - Arthur, Diane (HarperCollins Leadership, an imprint of HarperCollins, 2019)
A genuine classic, Recruiting, Interviewing, Selecting and Orienting New Employees is a practical guide to the employment process. Extensively revised, it contains forms, guidelines, and ready-to-use interview questions as well as advice on reference checking, interview methods, documentation issues, orientation programs, and applicant testing. -- Publisher